Functioning of the healthcare system in Poland – interest and self-assessed level of knowledge of the surveyed - Owoc, Alfred; Bojar, Iwona; Owoc, Jakub; Pawełczak-Barszczowska, Adrianna (Polish Journal of Public Health, 2009)
Aim. The objective of the analysis was to assess interest and self-assessed level of knowledge of how the Polish health care system works. Material and methods. The research was conducted in January 2008 among various social groups from five regions: Mazowieckie, Zachodniopomorskie, Śląskie, Lubuskie i Lubelskie. The author’s questionnaire was used as a research tool. 1200 questionnaires have been distributed and 711 ones have been correctly filled out and submitted. The results were statistically analyzed.  Results. 50% of those surveyed are not interested in issues concerning the health care system reform. Half of the surveyed thinks that their knowledge of how the system functions is suffi cient and 43% considers it too poor. The higher level of education the more interested are the surveyed in the health care system issues. Older individuals are more self-aware of their level of knowledge. Basic sources of information on the health care system are radio, television and press. A high rate of the surveyed (40.37%) believes that a modern health care is the government’s most important duty.